2013
DOI: 10.1111/jace.12193
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Atmosphere and Substrate Effects on the Phase and Texture of Chemical Solution Deposited Strontium Niobate Thin Films

Abstract: Strontium niobate (Sr:Nb = 1:1) thin films were prepared via chemical solution deposition on (001)‐oriented SrTiO3, (001)p‐oriented LaAlO3, (0001)‐oriented sapphire, and polycrystalline alumina substrates. Crystallization in oxygen at 1000°C yielded Sr2Nb2O7 films on all substrates with strong (010) orientation. Films on LaAlO3 and SrTiO3 single‐crystal substrates possessed a small amount of preferred in‐plane orientation, whereas films prepared on sapphire and polycrystalline alumina substrates were fiber tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…[9][10][11][12] Ceramics with composition Sr x NbO 3 were first investigated in the 1950s 13,14 and it was reported that a single-phase cubic perovskite is formed for 0.70 < x < 0.95 and these perovskites are found to be metallic conductors down to 4 K. Since the last decade, the perovskites SrMO 3 (M = Ti, V, Zr, and Nb) attract much attention from physicists and material scientists because of the unusual combination of their magnetic, electronic, and transport properties. [15][16][17][18][19] Among these the preparation of Sr II Nb IV O 3 crystal phase with cubic perovskite structure might be difficult as Nb ion prefers to exist in 5+ oxidation state rather than 4+ oxidation state. 20 In recent past, it was clearly demonstrated the use of Sr 1Àx NbO 3 (0.1 ≤ x ≤ 0.2) as an effective photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Ceramics with composition Sr x NbO 3 were first investigated in the 1950s 13,14 and it was reported that a single-phase cubic perovskite is formed for 0.70 < x < 0.95 and these perovskites are found to be metallic conductors down to 4 K. Since the last decade, the perovskites SrMO 3 (M = Ti, V, Zr, and Nb) attract much attention from physicists and material scientists because of the unusual combination of their magnetic, electronic, and transport properties. [15][16][17][18][19] Among these the preparation of Sr II Nb IV O 3 crystal phase with cubic perovskite structure might be difficult as Nb ion prefers to exist in 5+ oxidation state rather than 4+ oxidation state. 20 In recent past, it was clearly demonstrated the use of Sr 1Àx NbO 3 (0.1 ≤ x ≤ 0.2) as an effective photocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…At this defect density (9 slabs of the n = 5 phase versus 34 slabs of n = 4 present within the left image), we calculate that there is a small amount of oxygen reduction by δ = 0.05 in the Sr 2− x La x Nb 2 O 7−δ samples. To confirm our results were not sensitive to this low level of reduction, an additional sample ( x = 0.1, approximately 220 nm thick) was prepared through CSD, but done so in oxidizing atmospheres to discourage the formation of the n = 5 slabs …”
Section: Resultsmentioning
confidence: 61%
“…Minority peaks associated with the 002 and 151 reflections were also observed, but constituted less than 3% of the diffracting volume based upon comparison of measured intensities and those expected from a random powder pattern. In previous work these films were shown to possess a random in‐plane orientation and therefore are fiber‐textured. Also, while we utilize single crystalline substrates in this study, (010)‐fiber texture was identified on non‐lattice‐matched and polycrystalline substrates, demonstrating a preferred (010) out‐of‐plane orientation regardless of substrate, which makes this technique/materials system uniquely manufacturable for thermal applications.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations